Novas ferramentas de processamento de sinais para a análise da cultura de neurônios corticais cultivados em dispositivos multieletrodos - Marques, Suélen Moreira (2012)
This dissertation analyses the electrical activity recorded in experiments involving the maturation of dissociated embryonic hippocampal cultures, using Multielectrode Array (MEA) devices, starting from the moment of the culture s placement in the device until its death, a period of 0 to 88 days in vitro (DIV). Classical spike analysis is applied to differents cultures, showing the progression of spikes and bursts . Particular attention is devoted to the last step associated with cellular death, as an unexpected rise in electrical activity amplitude is observed. In addition, other techniques such as Fourier Transform, Autocorrelation, Power Spectral Density, Peak Detection, Coherence, Detrended Fluctuation Analysis (DFA), Stacionarity and Gaussian were applied. It s possible to observe, from DIV 08 to DIV 28, by classical analysis of spikes, DFA, Stacionarity and Gaussian, culture is predominantly stationary and gaussian and there is variability in the behavior of channels showing long-range correlation. Analyzing the DIV 29 to 71 we could observe that the culture stabilizes like white noise and displaying electrical activity not stationary and not gaussian. In the later stages of development (DIV\'s 72 to 88) there is a disruption of electrical activity followed by an unexpected increase in the amount of spikes and bursts and, subsequently, cell death occurs.